Variasi Parameter Filed of View (FoV) terhadap Nilai Signal to Noise Ratio (SNR) Dan Contras to Noise Ratio (CNR) pada Pemeriksaan Lumbal Dengan Potongan Axial - Zofi Dwi Prihatini; Ni Nyoman Ratini; I Putu Tedy Indrayana; Gusti Ngurah Sutapa; I Wayan Supardi; I Gde Antha Kasmawan (Kappa Journal, 2025)
Magnetic Resonance Imaging (MRI) is widely used to evaluate spinal pathology, with image quality strongly influenced by acquisition parameters such as the Field of View (FOV). This study investigates the effect of small FOV adjustments on the Signal-to-Noise Ratio (SNR) and Contrast-to-Noise Ratio (CNR) in axial T2-weighted Fast Spin Echo (FSE) lumbar spine MRI. This study offers one of the quantitative evaluations of clinically realistic FOV variations, addressing a gap between routine protocol adjustments and evidence-based image quality optimization. This experimental study prospectively examined thirty patients undergoing routine lumbar spine MRI using a Philips Ingenia CX 1.5T system. Axial T2-weighted FSE images were acquired with three FOV settings (170 mm × 170 mm, 190 mm × 190 mm, and 210 mm × 210 mm), while all other imaging parameters were kept constant. Image quality was assessed by measuring mean signal intensities in standardized regions of interest (ROIs) placed in the intervertebral disc, cerebrospinal fluid (CSF), and surrounding fat tissue, from which SNR and CNR were calculated and statistically compared across FOV settings. The results showed increasing trends in SNR and CNR with larger FOV values; however, these differences were not statistically significant (p > 0.05), indicating that small FOV enlargements produce minimal voxel size changes and negligible effects on image quality. Clinically, these findings suggest that minor FOV adjustments can be safely applied to accommodate patient anatomy or positioning without compromising image quality, while larger FOV changes are required to achieve meaningful improvements in SNR and CNR.